Ophiorrhiza fangdingii (Rubiaceae), a New Record for the Flora of Vietnam - Quang, Pham Van; Thanh, Nguyen Trung; Truong, Do Van; Thuy, La Thi (VNU Journal of Science: Natural Sciences and Technology, 2019)
Ophiorrhiza fangdingii H.S. Lo, a species endemic to Guangxi, China, is newly reported for the flora of Vietnam. In addition to the information on ecology, phenology and taxonomic notes, the morphological characters of the capsule are firstly described based on the specimens collected in Vietnam. Keywords New record, Ophiorrhiza fangdingii , Rubiaceae, Vietnam. References [1] S.P. Darwin, The Pacific species of Ophiorrhiza L. (Rubiaceae), Lyonia. 1 (1976) 47. [2] C. Tao, C.M. Taylor, Ophiorrhiza in Flora of China, Science Press, Beijing & Missouri Botanical Garden Press, St. Louis, Volume 19, 2011. [3] G. Krishnakumar, K.B. Rameshkumar, S. Priya, K. Satheeshkumar, P.N. Krishnan, Estimation of camptothecin and pharmacological evaluation of Ophiorrhiza prostrata D. Don and Ophiorrhiza mungos L.,Asian Pacific Journal of Tropical Biomedicine. 2 (2012) 731. [4] K. Saito, H. Sudo, M.Yamazaki, M. Koseki Nakamura, M. Kitajima, H. Takayama, N. Aimi, Feasible production of camptothecin by hairy root culture of Ophiorrhiza pumilla, Plant Cell Reports. 20 (2001) 271. [5] D.B. Deb, D.C. Mondal, Taxonomic revision of the genus Ophiorrhiza L. (Rubiaceae) in Indian subcontinent Ophiorrhiza L. (Rubiaceae) in Indian subcontinent, Bulletin of the Botanical Survey India. 39 (1997) 148. [6] H.S. Lo, Ophiorrhiza in Flora Republicae Popularis Sinicae, Science Press, Beijing, Volume 71(1), 1999, 110-174, [7] H.S. Lo, Taxonomic revision of the Chinese species of Ophiorrhiza (Rubiaceae), Bulletin of Botanicial Research North-Eastern Forestry Institute. 10 (1990) 82. [8] J. Pitard, Ophiorrhiza in Flore Generade de l’Indo-Chine, volume 3, Masson, Paris, 1923. [9] H.H. Pham, OphiorrhizainAn Illustrated Flora of Vietnam, volume 3, Young Publishing House, Ho Chi Minh, 2003 (in Vietnamese) [10] W.G. Craib, Caprifoliaceae & Rubiaceaein Florae SiamensisEnumeratio, Siam Society, Bangkok, Volume 2(1), 1932, 253.